1996
DOI: 10.1007/bf00227264
|View full text |Cite
|
Sign up to set email alerts
|

Digit removal leads to discrepancies between the structural and functional organization of the forepaw barrel subfield in layer IV of rat primary somatosensory cortex

Abstract: The physiological representation of the forepaw in rat primary somatosensory cortex (SI) is topographically organized. This representation is associated with the unique arrangement of barrels in layer IV of the forepaw barrel subfield (FBS) in SI and provides an example of a relationship between cortical structure and function. It has been reported that removal of peripheral afferent input to the FBS prior to postnatal day 5 or 6 results in a disorganized FBS, while deafferentation at later times produces litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 26 publications
5
12
3
Order By: Relevance
“…Whereas the widths of both D2 and D4 activations did not change, the distance between their peak signals was significantly reduced to 0.9 ± 0.2 mm (p < 0.01, two-tailed unpaired t-test). This is consistent with the literature indicating that the nearby digit representations expand and take over the representation of the amputated digit (McCandlish et al, 1996). This can also be seen from the averaged profiles, crossing the centers of D2 and D4 activations in layer IV, from the correlation coefficient maps (Fig.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Whereas the widths of both D2 and D4 activations did not change, the distance between their peak signals was significantly reduced to 0.9 ± 0.2 mm (p < 0.01, two-tailed unpaired t-test). This is consistent with the literature indicating that the nearby digit representations expand and take over the representation of the amputated digit (McCandlish et al, 1996). This can also be seen from the averaged profiles, crossing the centers of D2 and D4 activations in layer IV, from the correlation coefficient maps (Fig.…”
Section: Resultssupporting
confidence: 93%
“…The well-defined relationship between the cortical barrels and the forepaw digits makes this system a good model for the study of neural function and plasticity. For example, it has been reported that removal of a peripheral afferent input to the forepaw barrel subfield prior to postnatal day 5 or 6 results in a disorganized forepaw barrel subfield, whereas deafferentation at later times produces little or no alteration of the forepaw barrel subfield (Dawson and Killackey, 1987; McCandlish et al, 1996). Although the representation of digit columns has been investigated by optical imaging of intrinsic signals (Gochin et al, 1992) and electrophysiological studies (Li et al, 1996; McCandlish et al, 1996), non-invasive mapping remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…The reorganization observed is similar to those observed previously in this system (Hickmott and Merzenich 2002) and in other systems after denervation or amputation (e.g., McCandlish et al 1996;Merzenich et al 1983). A very rapid initial shift in the border was followed by a more protracted shift (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…A major advantage of using BOLD fMRI for such studies would be the ability to study individual animals longitudinally. Specifically, studies of the changes in the functional boundaries using BOLD fMRI should further studies about the mechanism of neuronal reorganizations (Godde et al, 1996; McCandlish et al, 1996; Melzer et al, 1998; Godde et al, 2002; Calford, 2002). Furthermore, future clarifications of the spatial coupling between the neuronal activity and the physiological phenomena underlying the fMRI BOLD should help advance the understanding of the neuronal basis of fMRI.…”
Section: Discussionmentioning
confidence: 99%